Determinasi Price to Book Value dan Volume Perdagangan terhadap Harga Saham: Studi pada Emiten IDX30 - Fitriasari, Pipin; Yanida, Maria; Agustinawati, Ni Putu (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the determinants of stock prices by examining the influence of price to book value (PBV) and trading volume on companies listed in the IDX30 index. The research population includes all issuers consistently included in the IDX30 during the 2021–2023 period. Using a purposive sampling technique, 20 companies were selected, resulting in 60 observational data points. The data were analyzed using multiple linear regression accompanied by classical assumption tests to ensure the validity of the estimated model. The empirical results show that price to book value has a significant positive effect on stock prices, indicating that companies with higher PBV tend to exhibit stronger stock valuations. In addition, trading volume is also found to significantly influence stock prices, implying that increased liquidity and market activity contribute to higher investor demand and subsequent price appreciation. These findings highlight the relevance of fundamental valuation ratios and market activity indicators in explaining stock price movements within highly liquid and large-cap companies included in the IDX30 index.